ผลตอบแทนและต้นทุนทางเศรษฐศาสตร์การปลูกยาสูบพันธุ์เบอร์เลย์ ในตำบลทับผึ้ง อำเภอศรีสำโรง จังหวัดสุโขทัย: Return and Economic Cost of Burley Tobacco Production in Tubpeung Subdistrict, Srisumrong District, Sukhothai Province - Jaroensathapornkul, Jirawat (Asian Health, Science and Technology Reports, 2010)
Sukhothai Province has been a vital area of burley tobacco production up to the present period. Futther, the amounts of output are derived mainly from Srisumrong District. The numbers of farmers are also concentrated on Tubpeung Subdistrict. It enkindled me to investigate the tobacco production in such area. The main purpose of my research was to analyze the return and economic cost of burley tobacco production. According to the research methodology, the sample size was accounted for 53 farmers that drawn randomly from 3 villages. The important results revealed that the net average return on burley tobacco production was approximately equal to -6,715.29 baht per rai in the crop year of 2008/2009. Obviously, the crucial cost of production devoted to the labor input that was accounted for 59.98%. Within this, the cash and non-cash cost was accounted for 34.87% and 65.13% respectively. Apart from this, when the samples were separated into two groups: < 10 rais and 10 rais. The main results remained the same in the way of getting loss of tobacco production. The net average return on production was approximately equal to -8,326.33 and -6,409.72 baht per rai respectively. It will lead policy recommendation to the issue of tobacco planted area reduction, if the farmers realize the opportunity cost of labor input. In the long run the farmer should therefore adjust the structure of cultivated area. Ultimately, the vegetable production should be replcaed on the planted area of burley tobacco.